Research and development of anti-maceration laparoscopic surgical cotton swabs. Issue 4 (1st April 2022) - Fujii, Shota; Ishii, Yuji; Katsuyama, Shinsuke; Akai, Kazutaka; Ueda, Tomoya; Inada, Mitsuru; Fukushima, Akihiro; Nakajima, Kiyokazu
Abstract: Introduction: Although laparoscopic cotton swabs have been used in procedures such as blunt tissue dissection and elevation of organs, fluid maceration is widely known to reduce their original performance. Thus, we developed an anti-maceration laparoscopic surgical cotton swab that is expected to solve this problem by coating the cotton swab with water-resistant resin. This study aimed to determine whether anti-maceration cotton swabs perform better than conventional products. Material and methods: Fine surface shape analysis of cotton swabs was performed using microfocus X-ray computed tomography, and changes due to fluid absorption of the anti-maceration cotton swabs and pre-existing products were quantitatively compared. As indices, the degree of expansion by maceration and SMD (surface roughness index of the fiber industry showing the size of irregularities on the surface) were evaluated. Results: The degree of expansion was lower in anti-maceration swabs than in conventional products. Maceration reduced SMD in existing products, whereas the SMD in anti-maceration cotton swabs did not change. Conclusions: Anti-maceration cotton swabs have a superior performance over conventional products.